A new SOGI-PLL method based on fuzzy logic for grid connected PV inverter - abdelhadi bouknadel; Naima Ikken; Ahmed Haddou; Nour-Eddine Tariba; Hafsa El omari; Hamid El omari (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Phase angle detection of the grid voltage is an imperative part of control in most applications, especially for the synchronization of the current injected by the grid-connected photovoltaic inverters. Consequently, fast and accurate detection of the phase angle, frequency and amplitude of the grid voltage are indispensable data to ensure a correct generation of reference signals and operation of the grid connected inverters. We present in this work a new phase-locked loop (PLL) method for single-phase systems. The novelty is to generate an orthogonal voltage system using a second-order generalized integrator (SOGI), followed by a Park transformation, whose quadrature component is forced to zero by the fuzzy logic, in order to obtain rapid detection and a more accurate picture of the phase angle. Furthermore, simulation results with PSIM software will be submitted to verify the performance and effectiveness of the proposed method strategy. Finally, the experimental test will be used to extract the result and discuss the validity of the proposed algorithm.